The Immigration Act 2016 - Davies, A (Oxford University Press, 2016)
This note considers the labour law provisions of Part 1 (sections 1-38) of the Immigration Act 2016. These have received relatively little critical attention, perhaps because of the focus on the Trade Union Act 2016, which was going through Parliament at much the same time. The labour law provisions of the Act fall into four main groups: the creation of the new office of Director of Labour Market Enforcement (LME), reforms to the Gangmasters Licensing Authority (GLA), the creation of LME undertakings and orders (with a criminal offence for breach), and the amendment of criminal offences relating to illegal working. Most of these provisions enter into force from 12 July 2016, with the exception of those relating to LME undertakings and orders, which have not yet been given a commencement date. These powers are to be used in accordance with a statutory code of practice which has not yet been drawn up.